Some estimates of the engel function for various comodities in Malaysia - Sritua Arief (Penerbit Universiti Kebangsaan Malaysia, 1982)
Six models of the Engel function were used to estimate household consumption patterns in Malaysia based on the data of the Household Expenditure Survey of 1973. A total of 18 groups of consumption items were analyzed including rice, bread, meat, fish, sugar and others. The study found that the suitability of each model varies according to identified product groups.